1987
DOI: 10.1002/mpo.2950150210
|View full text |Cite
|
Sign up to set email alerts
|

Malignant histiocytosis in infants: Surface marker analysis of malignant cells in two cases

Abstract: Two infants with malignant histiocytosis, as diagnosed by morphological and cytochemical examinations of malignant cells infiltrating pleural effusion, skin, and bone marrow, are described. Surface marker analysis of the malignant cells with monoclonal antibodies showed these cells to express markers of T-lymphocytes and HLA-DR antigen, but not those of B-lymphocytes, granulocytes, or monocytes. These immunological findings demonstrated that the neoplastic cells in malignant histiocytosis of infancy may be of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Risdall et al [16] and Manoharan and Catovsky [28] analyzed the morphological differences between histiocytic cells found in both bone marrow and lymph nodes of patients with VAHS or MH. We have previously reported on the histological and im munological features of histiocytic cells in MH [29]. In this study, we classified each patient as having either VAHS or MH as suggested by these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Risdall et al [16] and Manoharan and Catovsky [28] analyzed the morphological differences between histiocytic cells found in both bone marrow and lymph nodes of patients with VAHS or MH. We have previously reported on the histological and im munological features of histiocytic cells in MH [29]. In this study, we classified each patient as having either VAHS or MH as suggested by these previous reports.…”
Section: Discussionmentioning
confidence: 99%